Theological Criticism of Qadariyah and Jabariyah in Maziyyah by KH. Ambo Dalle: The Perspective of Islam in the Indonesian Archipelago - Fadel, Achmad; Mubarak, Ahmad Yusuf; Khaerussalam, Ahmad; Umar, Ahmad; Tanggok, M. Ikhsan (Tashwirul Afkar, 2023)
This study analyses the theological criticism of KH. Abdurrahman Ambo Dalle towards the two extreme schools of Islamic theology (Jabariyyah and Qadariyyah) while mapping the moderate position of Ahl al-Sunnah wa al-Jamā’ah (ASWAJA) as articulated in his work Maziyyah Ahl al-Sunnah wa al-Jamā’ah Bayna al-Niḥal wa al-Firaq al-Mubtadi’ah. The research is significant in that it offers a Nusantara Islam perspective on the classical theological debate concerning human free will and divine predestination. Employing a qualitative textual approach, the study applies thematic analysis and contextual hermeneutics to a classical text written in Bugis, supported by relevant academic literature. The findings demonstrate that Ambo Dalle constructs a theological typology in which ASWAJA occupies a moderate axis through the concept of kasb-humans as morally accountable agents, though the power to act originates from God. The proportional spectrum between divine predestination, human volition, and moral responsibility systematically illustrates the integrative theological model of ASWAJA. These findings have practical implications for strengthening the narrative of moderate Islam in Indonesia, especially within the pesantren curriculum and the discourse of Islam Nusantara. The originality of this study lies in its contextual reading of local theological thought, which remains underexplored in global scholarship, offering a reflective integration of classical theology with lived expressions of local Islam.